2020
DOI: 10.1038/s41598-020-67271-4
|View full text |Cite|
|
Sign up to set email alerts
|

Sex dependent effects of post-natal penicillin on brain, behavior and immune regulation are prevented by concurrent probiotic treatment

Abstract: There is increasing awareness of the need to consider potential long-term effects of antibiotics on the health of children. In addition to being associated with immune and metabolic diseases, there is evidence that early-life antibiotic exposure can affect neurodevelopment. Here we investigated the effect of low dose of penicillin V on mice when administered for 1 week immediately prior to weaning. We demonstrated that exposure to the antibiotic during the pre-weaning period led to long-term changes in social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
(86 reference statements)
1
9
0
1
Order By: Relevance
“…In addition to early life being of critical importance in terms of disruptive antibiotic effect on gut microbiota, antibiotic studies on adult animals also showed impaired behavior and brain function [ 71 , 83 , 93 , 94 , 95 ] and neurodegenerative disorders [ 96 ] both in prolonged and short courses, supporting the crucial role of gut microbiota-brain axis during lifespan. Some of the studies showed that these disruptive effects can be rescued by probiotic administrations [ 89 , 97 ].…”
Section: Impact Of Antibiotic Use On Gut Microbiome-brain Axismentioning
confidence: 99%
“…In addition to early life being of critical importance in terms of disruptive antibiotic effect on gut microbiota, antibiotic studies on adult animals also showed impaired behavior and brain function [ 71 , 83 , 93 , 94 , 95 ] and neurodegenerative disorders [ 96 ] both in prolonged and short courses, supporting the crucial role of gut microbiota-brain axis during lifespan. Some of the studies showed that these disruptive effects can be rescued by probiotic administrations [ 89 , 97 ].…”
Section: Impact Of Antibiotic Use On Gut Microbiome-brain Axismentioning
confidence: 99%
“…We assessed gene expression in the hippocampus of mice 32 days following CSD, with and without post-defeat JB-1 and sertraline treatment; targeting genes related to stress response, social behavior and memory that had been previously identified as being modulated by JB-1 in other models 17 , 20 , 21 . For corticotropin-releasing hormone receptor subtypes (CRHR-1 and -2) and arginine vasopressin (AVPR-1a and -1b) in the hippocampus, we found that mice treated with JB-1 or sertraline had significantly lower expression of CRHR-1 mRNA relative to mice in defeat control group (F (2, 15) = 1.391, η 2 p = 0.16, defeat control: 0.81 ± 0.097, JB-1: 0.37 ± 0.049, g = 2.32, p = 0.0020; sertraline: 0.44 ± 0.061, g = 1.88, p = 0.0069) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Early life concurrent administration of L. rhamnosus JB-1 to antibiotic-treated pregnant dams until weaning decreased anxiety-like behavior in female offspring, and prevented antibiotic-associated deficits in sociability [ 136 ]. Administering L. rhamnosus JB-1 to antibiotic-treated offspring one week prior to weaning prevented the antibiotic-associated effects, such as deficits in social behavior (but not on anxiety-like behavior), changes in gene expression in specific brain regions, and changes in immune cell populations in the spleen [ 183 ].…”
Section: Psychobiotics—selected Case Studies Of Translational Results...mentioning
confidence: 99%